(untitled) (Cadernos de Sociomuseologia, 2015)
In the present article, written as part of the doctoral researchthat I am conducting is intended to analyze the impact of newtechnologies of communication and information in the change ofthe communication paradigm of museum institutions, toprioritize one ubiquitous, participatory, and relevant museology. Keywords:Museology, social media participation, digital collections,communication